Letter: previous exposure to corticosteroids increases the risk of post‐discharge venous thromboembolic events in patients with inflammatory bowel disease—author's reply. Issue 6 (27th August 2019) - McCurdy, Jeffrey D
Abstract : LINKED CONTENT This article is linked to McCurdy et al and Zeng and Gan papers. To view these articles, visit https://doi.org/10.1111/apt.15286 and https://doi.org/10.1111/apt.15411 .